GENICULAR NERVE ABLATION IN KNEE OSTEOARTHRITIS: A RANDOMIZED PROSPECTIVE STUDY - João Vital Arthur Maradona Oliveira Dias; Vitor Ricardo Alves Pereira de Moraes; Matheus Trindade Bruxelas de Freitas; Matheus Manolo Arouca; Guilherme Pereira Ocampos; Olavo Pires de Camargo; Márcia Uchoa de Rezende (Acta Ortopédica Brasileira)
ABSTRACT Objective: To document the effects of genicular nerve ablation in patients with severe knee osteoarthritis (OAJ) at 1 and 3 months. Methods: Prospective, randomized, and controlled trial with 35 patients with grade IV knee osteoarthritis according to Kelgren & Lawrence, undergoing genicular nerve ablation with pulsed radiofrequency (PRF) or phenol. Outcomes were assessed at baseline, 1 month, and 3 months using the Numeric Rating Scale (NRS), the Knee Injury and Osteoarthritis Outcome Score (KOOS), the 30-Second Chair Stand Test (TSL30), and the Timed Up and Go (TUG) test. Results: The groups were similar at baseline. Both groups improved similarly up to 3 months (p<0.001). NRS decreased by an average of 30% from baseline to all subsequent assessments (p<0.05). TUG decreased between baseline and one month post-procedure (p=0.001), while TSL30 increased from baseline to one and three months (p<0.05). The average behavior of patients was equal between groups over the evaluations for all scores (p Interaction > 0.05). None of the scores differed between groups, regardless of the evaluation period (p Group > 0.05). Conclusions: Genicular nerve ablation in patients with severe OAJ can provide lasting improvements in pain, function, and quality of life. Both methods, phenol and radiofrequency, are effective. Level of Evidence I; Controlled Randomized Clinical Trial.